2012
DOI: 10.2147/ijn.s33773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of buckminsterfullerenes on cells of the innate and adaptive immune system: an in vitro study with human peripheral blood mononuclear cells

Abstract: C60 nanoparticles, the so-called buckminsterfullerenes, have attracted great attention for medical applications as carriers, enzyme inhibitors or radical scavengers. However, publications evaluating their immunological mechanisms are still rather limited.Therefore, we aimed to analyze systematically the in vitro influence of polyhydroxy-C60 (poly-C60) and N-ethyl-polyamino-C60 (nepo-C60) on peripheral blood mononuclear cells (PBMC) from healthy individuals, angling their effect on proliferation, expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Some studies showed that C 60 have immunostimulatory properties [ 28 30 , 103 , 106 ]. After instillation, C 60 upregulated gene expression of various proinflammatory cytokines (IL-1, TNF- α , IL-6) and Th1 cytokines (IL-12,IFN- γ ) in mice.…”
Section: Immunomodulation By Different Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that C 60 have immunostimulatory properties [ 28 30 , 103 , 106 ]. After instillation, C 60 upregulated gene expression of various proinflammatory cytokines (IL-1, TNF- α , IL-6) and Th1 cytokines (IL-12,IFN- γ ) in mice.…”
Section: Immunomodulation By Different Npsmentioning
confidence: 99%
“…The carboxyfullerene could prolong the infiltrating neutrophils to enhance the bactericidal activity of neutrophils [ 30 ]. Other studies indicated that fullerene may enhance the ability of DCs to stimulate T cells and furthermore activated cells of innate immune system by enhancing production of IL-6 and an activation of natural killer (NK) cells [ 103 , 106 ]. In addition, immunization of mice with a C 60 fullerene derivative conjugated to bovine thyroglobulin could produce a population of fullerene-specific antibodies, which included a subpopulation that cross-reacted with a C 70 fullerene [ 29 ].…”
Section: Immunomodulation By Different Npsmentioning
confidence: 99%
“…89,90 Water-soluble fullerenes can successfully pass through the cell membrane and serve as intracellular delivery agents. 90,91 To mitigate oxidative damage to cells and tissues, polyhydroxylated fullerenes (a.k.a. fullerenols), with radical scavenging ability, have been used to deliver doxorubicin (DOX), a widely used chemotherapeutic drug.…”
Section: Drug and Gene Deliverymentioning
confidence: 99%